Parasitic plants of the genus Cuscuta and their interaction with susceptible and resistant host plants - Kaiser, Bettina; Vogg, Gerd; Fürst, Ursula B.; Albert, Markus (Frontiers in Plant Science, 2015)
By comparison with plant-microbe interaction, little is known about the interaction of parasitic plants with their hosts. Plants of the genus Cuscuta belong to the family of Cuscutaceae and comprise about 200 species, all of which live as stem holoparasites on other plants. Cuscuta spp. possess no roots nor fully expanded leaves and the vegetative portion appears to be a stem only. The parasite winds around plants and penetrates the host stems via haustoria, forming direct connections to the vascular bundles of their hosts to withdraw water, carbohydrates and other solutes. Besides susceptible hosts, a few plants exist that exhibit an active resistance against infestation by Cuscuta spp. For example, cultivated tomato (Solanum lycopersicum) fends off Cuscuta reflexa by means of a hypersensitive-type response occurring in the early penetration phase. This report on the plant-plant dialogue between Cuscuta spp. and its host plants focuses on the incompatible interaction of Cuscuta reflexa with tomato.